Performance analysis of non-linear constellation precoded NOMA over Rayleigh fading channel - Narasimman Manogaran; Muthuchidambaranathan Palanivel (Results in Engineering)
Non-orthogonal multiple access (NOMA), an advanced technology for 5G and beyond, has emerged as a promising solution to address the escalating wireless data traffic and enhance the efficiency of wireless systems. Nonlinear constellation precoding (NCP) improves the diversity gain using the maximum distance separable codes property. In this paper, we propose a novel (NCP-NOMA) scheme to enhance the diversity performance of the NOMA system. NCP pre-codes the far user (FU) and near user (NU) data separately and the binary codeword is obtained. The codeword is then subjected to QAM modulation, followed by superimposing the FU and NU codewords for NOMA transmission. This paper investigates the performance of the proposed system in terms of bit error rate (BER) for FU and NU using Monte Carlo simulation and compares the results with the conventional NOMA scheme. The simulation results demonstrate that integrating the NCP encoder achieves a 6dB diversity gain, resulting in a BER of 10−3.